Crecimiento economico, convergencia y disparidades regionales en el peru - Roncal Rodríguez, Franklin Santiago (2016)
A development management has been a topic that has motivated debates in the political and academic spheres. Even though this situation has enriched the discussion, it has not brought up potential actions to increase the well-being in most of the population. The economic results of the country show exceptional growth levels of GDP in the last ten years, averaging an annual rate of 5.3%, an accumulated growth, first time ever in history, of 59.7%. Although these economic growth rates are very important, the regional incomes have not been distributed in pace with the national growth. In this context, inequality and regional disparity take place. The issue why some economical activities focus on specific areas leads us to the following question: Is there a tendency for growth of the poorest regions and therefore to a convergence; or if the dispersion of real income per capita across regional economies shows a decreasing trend, making a country be more equitable? Following an analysis of the regions at different periods of time -- analysis of dispersion, speed, approach and distance – some results confirm that, far from showing a reduction on regional disparities, this is a process to multiple converging relativisations depending on the geographical context.